In the Sign of Bear - Marcelli, Miroslav (Iluminace, 2001)
A review of the American action film Ghost Dog - The Way of the Samurai by director Jim Jarmusch.
Keywords: Ghost Dog - Cesta samuraje 1999; recenze filmu